Constraints on the Mineralogy and Geochemistry of Vera Rubin Ridge, Gale Crater, Mars, From Mars Science Laboratory Sample Analysis at Mars Evolved Gas Analyses. Issue 11 (14th November 2020) - McAdam, Amy C.; Sutter, Brad; Archer, P. Douglas; Franz, Heather B.; Wong, Gregory M.; Lewis, James M. T.; Eigenbrode, Jennifer L.; Stern, Jennifer C.; Knudson, Christine A.; Clark, Joanna V.; Andrejkovičová, Slavka; Ming, Douglas W.; et al.
Abstract: Vera Rubin ridge (VRR) is a topographic high within the layers of Mount Sharp, Gale crater, that exhibits a strong hematite spectral signature from orbit. The Mars Science Laboratory Curiosity rover carried out a comprehensive investigation to understand the depositional and diagenetic processes recorded in the rocks of VRR. Sample Analysis at Mars (SAM) evolved gas analyses (EGA) were performed on three samples from the ridge and one from directly beneath the ridge. SAM evolved H2 O data suggested the presence of an Fe‐rich dioctahedral smectite, such as nontronite, in the sample from beneath the ridge. H2 O data are also consistent with ferripyrophyllite in VRR samples. SAM SO2 data indicated that all samples contained Mg sulfates and some Fe sulfate. Several volatile detections suggested trace reduced sulfur sources, such as Fe sulfides and/or S‐bearing organic compounds, in two samples while significant O2 and NO evolved from one sample indicated the presence of oxychlorine and nitrate/nitrite salts, respectively. The O2 evolution was the second highest to date and the first observed in ~1, 200 sols. HCl released from all samples likely resulted, in part, from trace chloride salts. All samples evolved CO2 and CO consistent with oxidized carbon compounds (e.g., oxalates), while some CO2 may result from carbonate. SAM‐derived constraints on the mineralogy and chemistry of VRR materials, in the context of additional mineralogy, geochemistry, and sedimentology information obtained by Curiosity, support a complex diagenetic history that involved fluids of a range of possible salinities, redox characteristics, pHs, and temperatures. Plain Language Summary: The Mars Science Laboratory Curiosity rover conducted a detailed study of the rocks that make up the Vera Rubin ridge (VRR) feature in Gale crater, Mars, to better understand Martian geologic history. The Curiosity rover's Sample Analysis at Mars (SAM), a suite of scientific instruments on the rover, measured several diagnostic gases when it was used to heat samples from on and beneath VRR. These gases provided information about the mineralogy and chemistry of VRR samples that, together with additional information from other instruments on the rover, indicated that several different types of fluids affected the rocks in the ridge over geologic time. These fluids varied in temperature, salt content, and acidity. Key Points: Vera Rubin ridge experienced a complicated diagenetic history involving alteration by fluids with a variety of chemistries and temperatures Sample Analysis at Mars instrument suite data support an Fe‐rich composition for phyllosilicates detected on and near Vera Rubin ridge Several salts were detected, including sulfate, chloride, nitrate, and oxychlorine salts, enabling constraints on diagenetic fluid chemistry